Unique alterations of an ultraconserved non-coding element in the 3'UTR of ZIC2 in holoprosencephaly - Roessler, Erich; Hu, Ping; Hong, Sung-Kook; Srivastava, Kshitij; Carrington, Blake; Sood, Raman; Petrykowska, Hanna; Elnitski, Laura; Ribeiro, Lucilene A; Richieri-Costa, Antonio; Feldman, Benjamin; Odenwald, Ward F; et al. (PloS one, 2012)
Coding region alterations of ZIC2 are the second most common type of mutation in holoprosencephaly (HPE). Here we use several complementary bioinformatic approaches to identify ultraconserved cis-regulatory sequences potentially driving the expression of human ZIC2. We demonstrate that an 804 bp element in the 3' untranslated region (3'UTR) is highly conserved across the evolutionary history of vertebrates from fish to humans. Furthermore, we show that while genetic variation of this element is unexpectedly common among holoprosencephaly subjects (6/528 or >1%), it is not present in control individuals. Two of six proband-unique variants are de novo, supporting their pathogenic involvement in HPE outcomes. These findings support a general recommendation that the identification and analysis of key ultraconserved elements should be incorporated into the genetic risk assessment of holoprosencephaly cases.